Schlüsselrolle Schulpraktika – Vergleich der Studierendenselbstwirksamkeit und der Wirksamkeitseinschätzung in den Pädagogisch-praktische Studien im Kontext der Einführung der Pädagog*innenbildung Neu an der PH Wien (Pedagogical Horizons, 2020)
School internships play a key role in teacher education (Arnold, Gröschner & Hascher, 2014). It must be critically examined whether they relate to the professional field, the development of the intended learning outcomes and whether they are demonstrably effective (Gottein, 2016). With the introduction of a new teacher education law at the University College of Teacher Education Vienna, the study area of pedagogical-practical studies was reconceptualized. This article compares the self-efficacy assessment and the assessment of the effectiveness of the pedagogical-practical studies, based on the results of an empirical-quantitative questionnaire survey conducted among the students in the sixth (n = 257, last semester of the old bachelor curriculum) and the eighth semester of education (n = 149; last semester of the new bachelor curriculum). The results are discussed in terms of study structure and impulses for the further curricular development of the pedagogical-practical studies are formulated.